The personality-oriented approach to teaching higher mathematics - Іщенко, Ольга Анатоліївна; Ищенко, Ольга Анатольевна; Ishchenko, Olha (Мелітополь: ТДАТУ, 2021)
UK: Розглянуто аспекти реалізації особистісно-орієнтованого підходу при викладанні вищої математики в закладах вищої освіти. Продемонстровано можливість використання технології рівневої диференціації на прикладі теми «Невизначений інтеграл», як методу реалізації такого підходу. EN: Implementation aspects of the personality-oriented approach to teaching Higher Mathematics in higher education institution are considered. Workability of the level differentiation technology under the topic «Indefinite integral» is demonstrated as a method for implementing this approach.
Keywords: особистісно-орієнтований підхід; заклади вищої освіти; технологія рівневої диференціації; вища математика; the personality-oriented approach; higher education institution; the level differentiation technology; higher mathematics